INSTITITUTIONAL SERVICE QUALITY AND ACADEMIC SATISFACTION OF HOSPITALITY AND TOURISM MANAGEMENT STUDENTS - Mercy Busayo BELLO; Amelia Jennifer Ofodu. (European Journal of Humanities and Educational Advancements, 2024)
The study explores the relationship between dimensions of institutional service quality and academic satisfaction in respect of students of Hospitality Management and Tourism, in institutions of higher learning South-South, Nigeria. Survey method was employed for the collection of data, while multiple regression was used for data analysis. The results reveal a positive and significant relationship between the five dimensions of institutional service quality and academic satisfaction of students of Hospitality Management and Tourism in institutions of higher learning South-South, Nigeria. However, the outcome of regression analysis shows that tangibility, reliability and responsiveness are the most positive predictors of academic satisfaction in respect of students of Hospitality Management and Tourism in institutions of higher learning South-South, Nigeria. Based on these findings, the researchers suggest that the management of higher institution of higher learning that offers HMT course in the South-South Nigeria should collaborate with stakeholders such as organised private sector and the government to provide facilities and structure that can help improve and deliver on service quality in our tertiary instructions hence, increase academic satisfaction of students.